OBSERVATIONS ON THE FISHERY AND BIOLOGY OF GRAMMOPLITES SCABER (LINNAEUS) - Kuthalingam, M D K (Indian Journal of Fisheries, 2011)
A preliminary study of the fishery and biology of Grammoplites scaber was madebased on the landings of M.V. Tarpon during the years 1962-64. Higher catch rates(40.4 - 62.4 kg/hr) were obtained in depths 40-55 m and in shallower waters the catchrates were poor (6.2-20.4 kg/hr); also the larger size groups of fishes occurred in deeperwaters. The sex ratio differed considerably according to depths. G. scaber feeds predominantlyon crustaceans and the prawn Parapenaeopsis stylifera appears to be thefavourite food of the fish above 142 mm.